Unconventional gas resources in the Cantabrian Zone (NW Spain): A comprehensive preliminary assessment. (14th September 2018) - Álvarez, Rodrigo; Ordóñez, Almudena; Canteli, Paula; De Miguel, Eduardo
Abstract : With the aim of acquiring a better knowledge of the potential for unconventional gas resources in Spain, 134 rock samples were taken from 12 lithostratigraphic units in the Cantabrian Zone (north‐west Spain) and studied for a 3‐year period. The selected units gather, a priori, the basic conditions to constitute potential source rocks for unconventional hydrocarbons. Petrographic studies and total organic carbon analyses were carried out for all samples, whereas Rock‐Eval pyrolysis and vitrinite reflectance measurements with kerogen visual analysis were performed on selected samples. Lutites, litharenites, limestones, and slates are the predominant petrographic types. In most cases, the mean total organic carbon content is below the 2% limit for good quality potential source rocks. Only the Jurassic Rodiles and Tereñes limestones show total organic carbon values above this threshold. Rock‐Eval data reveal very low potential for hydrocarbon generation in almost all cases, with the exception of the dark mudstones of the Carboniferous Barcaliente Formation and the Rodiles Formation (fair and good potential for hydrocarbon generation, respectively). As regards thermal maturation, only the Ordovician formations are located in the peak of the gas generation interval. The Barcaliente and Rodiles formations are near the frontier oil/wet gas maturation areas, and the rest of the units are immature for gas generation.